Toxic Sublime: The Spectacle of Ecological Collapse in Contemporary Art - Gladys Putri; Bimala Putri; Henrietta Noir; Jujuk Maryati (Enigma Institute, 2025)
In the era of the Anthropocene, a significant genre of contemporary art has emerged that engages with ecological collapse by rendering environmental devastation visually captivating. This phenomenon, which this paper terms the